THE EFFECT OF SUPERVISION, PROFESSIONALISM AND TEAMWORK ON EMPLOYEE PERFORMANCE OF PT. SARANA ABDI BAHAGIA MEDAN - Rosnaida, Rosnaida; Rahman, Abdul; Japina, Henky (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study aims to analyze the influence of supervision, professionalism, and team collaboration on employee performance at PT. Sarana Abdi Bahagia Medan. The sample consisted of 37 respondents. The research employed a descriptive quantitative approach using multiple linear regression analysis. The results indicate that supervision, professionalism, and team collaboration simultaneously have a significant impact on employee performance. Individually, each variable also contributes to performance improvement. The adjusted R square value of 0.584 implies that 58.4% of the variability in employee performance can be explained by the three variables, while the remaining 41.6% is influenced by other factors not examined in this study. Therefore, it can be concluded that supervision, professionalism, and team collaboration play a substantial role in enhancing employee performance at PT. Sarana Abdi Bahagia Medan